Migraine Management in the Emergency Department - Jiménez Tung, ilen (2020)
Migraine is a chronic neurovascular, episodic and multifactorial condition; It affects men and women in western countries. It is caused by genetic and environmental factors. The clinical presentation is going to be a recurrent headache, this can be pulsatile or not and can be associated with nausea, vomiting, photophobia or phonophobia. Neuroimaging studies are performed in the presence of red headache flags. The treatment of acute pain is determined according to the severity and frequency of migraine attacks and the taking or not of prior medication.